Optimalisasi Mutu Kinerja SDM (Ustadz) Pondok Pesantren di TMI Al-Amien Prenduan Madura - Moh Fahrun (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2023)
This article aims to describe the optimization of the performance quality of Islamic boarding school teachers at TMI Al-Amien Prenduan. This research uses a qualitative approach with a descriptive type. Sources of data were obtained through observation, interviews, and documentation. The results of the research show that the performance development process consists of disciplinary coaching, performance motivation, professional groups, internal associations, increasing education levels, and seminars/training/workshops. As for the performance appraisal process through evaluating the competence of ustadz in marhalah, namely the Education Teacher Group (KGBE), evaluating the competence of ustadz outside marhalah with Complete Teacher Meetings (RGL), Thursday meetings, and Riasah Board Oversight (PDR). Based on this description, it can be concluded that TMI Al-Amien Prenduan is very good at managing the quality improvement of ustadz. However, there is a shortage of data instruments for assessing the quality of ustadz performance, especially in the field of the development process and evaluating the performance of ustadz.